2021
DOI: 10.1016/j.evolhumbehav.2020.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Punishment is strongly motivated by revenge and weakly motivated by inequity aversion

Abstract: There are two broad functional explanations for second-party punishment: fitness-leveling and deterrence. The former suggests that people punish to reduce fitness differences, while the latter suggests that people punish in order to reciprocate losses and deter others from inflicting losses on them in the future. We explore the relative roles of these motivations using a pre-registered, two-player experiment with 2,426 US participants from Amazon Mechanical Turk. Participants played as the "responder" and were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…Most literature on laypeople's punishment motives suggests that individuals' punishment is best described as primarily retributive, rather than occurring for utilitarian purposes such as special prevention or general prevention [5,6,9]. More recent research, however, provides evidence against the ubiquity of retributive motives [16,17]. The present research adds to the debate on the motivational basis of punishment by investigating punishment motives from a developmental perspective.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Most literature on laypeople's punishment motives suggests that individuals' punishment is best described as primarily retributive, rather than occurring for utilitarian purposes such as special prevention or general prevention [5,6,9]. More recent research, however, provides evidence against the ubiquity of retributive motives [16,17]. The present research adds to the debate on the motivational basis of punishment by investigating punishment motives from a developmental perspective.…”
Section: Discussionmentioning
confidence: 78%
“…However, more recent research suggests that the ubiquity of this "people as retributivists" position may, at least partially, be limited to certain methodological aspects of the research [14,15]. Similarly, experiments studying punishment behavior in economic games revealed that punishment behavior is motivated by both retribution and special prevention [16,17]. Of particular relevance for the research at hand, scholars isolated people's punishment motives in a third-party punishment paradigm by manipulating the degree to which the punishment was communicated to the offenders and thus the extent to which it could entail any special preventive effects at all.…”
Section: Introductionmentioning
confidence: 99%
“…When an individual is free to contribute and punish as they want, they often become low contributors who punish hypocritically 40 . Punishing hypocritically increases rather than decreases inequity between individuals, challenging explanations based on inequity aversion [46][47][48][49][50] . These results contradict the Altruistic Punishment / Strong Reciprocity hypothesis and support the hypothesis that many individuals are initially confused in experiments but learn from experience to contribute less.…”
Section: Discussionmentioning
confidence: 99%
“…Seminal experiments have shown that punishment can be used to promote cooperation [6][7][8], though often at the expense of efficiency (for a review, see [25]; but see [53]). More recent experiments have instead demonstrated that punishment is, in many cases, motivated by revenge ( [30,31]; but see [54]), status concerns [55] or aversion to (disadvantageous) inequality [30,56]. Traditional views of gossip and ostracism have emphasized the dark side of these tactics, seeing them as means to indirectly aggress against peers [37,39], and to impose status costs via reputation manipulation ( [57][58][59]; especially in the context of resource competition, see [60] in this issue).…”
Section: Common and Unique Social Functions Of Distinct Punishment Tacticsmentioning
confidence: 99%
“…While punishment might be aimed at changing an offender's (future) behaviour, we do not consider deterrence as a necessary component of its definition. For example, punishers can aim at reducing disadvantageous inequality or creating advantageous inequality without deterrence [30,31], and they can reap reputational benefits independent of any recalibration of offenders' behaviour. Moreover, we use an inclusive definition of punishment that considers a host of tactics used to inflict costs on offenders, some of which require punishers to pay significant short-term costs, while others are less costly.…”
Section: Introductionmentioning
confidence: 99%